RELIGIOUS IDENTIFICATION AND SOCIAL DISTANCE BETWEEN RELIGIOUS GROUPS IN YOGYAKARTA - Cahyo Pamungkas (Humaniora, 2015)
This paper explains how political, religious, and economic changes in Yogyakarta affect the formation of religious identity and social distance between different religious groups. The strengthening of religious identity in this area took place in the period of the Diponegoro War (1825-1830) when religious issues were used in the mobilization against the Dutch colonialist. Then, the spread of Christianity in Java at the end of 19th led to several tensions between missionaries and several Islamic organizations, but never developed into communal violence. In 1930s, the relation between religious groups remain harmonious due to the development of tolerant culture and pluralism. During the 1980s, the use of religious identity grew both in urban and rural areas in line with social processes of modernization. Da’wat activities on Campus (Lembaga Dakwah Kampus) plays important roles in promoting religious life in urban areas. The 1998 political reform marked the rise of religious fundamentalist movements that to a certain degree contributes to social distance between religious groups.